2019
DOI: 10.31812/educdim.v53i1.3844
|View full text |Cite
|
Sign up to set email alerts
|

The Google Lens analyzing quality: an analysis of the possibility to use in the educational process

Abstract: Biology is a fairly complicated initial subject because it involves knowledge of biodiversity. Google Lens is a unique, mobile software that allows you to recognition species and genus of the plant student looking for. The article devoted to the analysis of the efficiency of the functioning of the Google Lens related to botanical objects. In order to perform the analysis, botanical objects were classified by type of the plant (grass, tree, bush) and by part of the plant (stem, flower, fruit) which is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…More recently, [19] conducted a study to investigate the possibilities of Google Lens as an IoT tool in biology classes in Ukrainian schools. They found that Google Lens had outstanding outcomes and should be used in teaching.…”
Section: The Iot In Educationmentioning
confidence: 99%
“…More recently, [19] conducted a study to investigate the possibilities of Google Lens as an IoT tool in biology classes in Ukrainian schools. They found that Google Lens had outstanding outcomes and should be used in teaching.…”
Section: The Iot In Educationmentioning
confidence: 99%
“…Many AREdu 2019 authors have addressed various aspects of AR technology, in particular: Ihor O. Arkhypov [8], Volodymyr O. Artemchuk [5], Zhanna I. Bilyk [22; 23; 24], Anzhela P. Boiko [6], Stanislav L. Bondarevskyi [13], Oleksandr Yu. Burov [5], Iryna I. Deinega [5], Andrii V. Іatsyshyn [5], Anna V. Іatsyshyn [5], Valeriia O. Kovach [5], Yaroslav M. Krainyk [6], Tetiana H. Kramarenko [7], Ivan V. Kravets [11], Olexander I. Kuchma [8], Yulii G. Kutsan [5], Olga V. Kuzyshyn [11], Olena O. Lavrentieva [8], Victor M. Lutsyshyn [11], Svitlana H. Lytvynova [5], Maiia V. Marienko [20; 25], Oksana M. Markova [13; 16; 28], Anna P. Megalinska [23], Lilia Ya. Midak [11]…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 lists the apps and provides details on their popularity at the time of download (spring 2021). Plant Net, Leaf Snap and Plant Snap were among the top four suggestions in the Google Store, Google Lens was selected due to its pre-installation on virtually all devices and its link to the widely used Google Search engine [ 18 ]; and Seek and iNaturalist, which both utilise the same database, were created through collaboration of the National Geographic Society and the California Academy of Sciences [ 19 ]. iNaturalist relies on a database and requires users to confirm identifications but can also provide “live” identification and has been used in this manner for this study.…”
Section: Methodsmentioning
confidence: 99%